The Role of the Central Tapanuli Regency Government in Supervising and Controlling Landslide-Prone Locations from a Siyasah Dusturiyah Perspec-tive (Case Study: Tapian Nauli Village) - Gunawan Pardede, Roy Sandi; Irwansyah, Irwansyah (IHSA Institute, 2026)
This study aims to analyze the role of the Central Tapanuli Regency Government in monitoring and controlling landslide-prone areas in Tapian Nauli Village and review its implementation from a Siyasah Dusturiyah perspective. Tapian Nauli Village is included in an area with a high level of landslide vulnerability due to geographical conditions such as steep slopes, minimal vegetation, and uncontrolled land-use changes. The local government, through the Regional Disaster Management Agency (BPBD), has important responsibilities in disaster mitigation, spatial planning supervision, and community empowerment. However, the implementation of these functions faces obstacles such as budget constraints, weak inter-agency coordination, low public awareness, and weak environmental law enforcement. From a Siyasah Dusturiyah perspective, the government's responsibility in monitoring disaster-prone areas is a form of implementation of the leadership mandate to uphold justice ('adl) and public welfare (maslahah 'ammah). Thus, disaster monitoring policies must be implemented based on the principles of responsibility, justice, and public participation in accordance with Islamic values ??in governance